Weaving Architecture Effects on Mechanical and Chemical Performance of Alkali-Treated Coconut Fiber Composites - Agus Choirul Arifin; Deni Nur Fauzi; Noorsakti Wahyudi; Agus Susanto; Pradhana Kurniawan; Yoga Ahdiat Fakhrudi; M. Shafwallah Al. Aziz (Jurnal E-Komtek, 2026)
This study examines the effect of fabric architecture and alkali treatment on the properties of coconut fiber–polyester composites as an alternative environmentally friendly material. Coconut fibers were treated with 15% NaOH for 2 hours and woven in basket weave and twill weave patterns. The composites were made using a vacuum-assisted resin infusion method with a fiber fraction of 40%, and compared with E-glass composites as a control. FTIR analysis showed a decrease in the intensity of the absorption band in the range of 1200–1300 cm⁻¹, indicating a reduction in lignin content after alkali treatment. The mechanical test results showed that the basket weave composite had higher tensile and flexural strengths, respectively, of 20.40 N/mm² and 78.45 N/mm², compared to the twill weave at 12.98 N/mm² and 52.31 N/mm². However, the highest impact resistance was obtained in the twill weave at 23.61 J/mm². The results of the study indicate that the weave architecture has a significant effect on the mechanical performance of the composite and has the potential to support the development of sustainable composite materials for engineering applications.